Conflicting Imaginary Places in a Local Environmental Dispute - Eddy, Elizabeth (Transformations, 2005)
In 2000, a local conflict on the Sunshine Coast emerged over a proposed road development. The three kilometer dirt road was bordered by a national park on one side, and on the other, by the new university campus and residential estate. The development of this road along its current route would place a permanent road barrier between the University campus nature reserve and the National Park, but would provide a second access road for the estate. A public meeting was arranged by the local shire council to discuss an alternative route supported by the University. This paper examines the debate about this proposal at the public meeting, to explain the basis upon which the local residents supported the developer’s plan to develop the road along its current route, against the natural values arguments put forward by the University for a wildlife corridor. It draws upon recent scholarship on environmental conflict to identify two distinct “imaginary places” which underpinned the conflicting positions in this debate, each of which attributed different meanings to the road and to the differing spatial boundaries in which the road was located.